Can a participatory organizational intervention improve social capital and organizational readiness to change? Cluster randomized controlled trial at five Danish hospitals. (14th August 2020) - Jakobsen, Markus Due; Clausen, Thomas; Andersen, Lars Louis
Abstract: A im: This study investigates the effect of a participatory organizational intervention on social capital and organizational readiness for change. D esign: Cluster randomized controlled trial. M ethods: In 2016, 27 departments from five hospitals in Denmark were randomly allocated at the department level to 1 year of participatory intervention (14 clusters, 316 healthcare workers) or a control group (13 clusters, 309 healthcare workers). The participatory intervention consisted of 2 × 2 hr workshops, where managers, 2–5 healthcare workers from each department, and the hospital's health and safety staff, developed action plans for implementing solutions for improving the use of assistive devices at the department throughout the 1‐year intervention period. Workplace social capital: (a) within teams (bonding); (b) between teams and nearest leaders (linking A); and (c) between teams and distant leaders (linking B) and organizational readiness for change were measured using questionnaires at baseline, 6, and 12 months. R esults: No group‐by‐time interaction occurred for any of the outcome measures. However, explorative post hoc analysis showed within‐group improvements in bonding and linking B social capital and organizational readiness for change following the participatory intervention. C onclusion: Participatory organizational interventions may improve social capital within teams and between teams and distant leaders and organizational readiness for change. Impact: Implementing participatory interventions at the workplace may be a cost‐effective strategy as they provide additional benefits, e.g., increased social capital and improved organizational readiness for change, that exceed the primary outcome of the intervention. Trial registration: ClinicalTrials.gov (NCT02708550) March 2016. Abstract : 目标: 这项研究调查了参与式组织干预对社会资本和组织变革准备的影响。 设计: 整群随机对照试验。 方法: 2016年，丹麦五家医院的27个科室被随机分配到为期一年的参与式干预组（14组，316名医护人员）或对照组（13组，309名医护人员）。参与式干预包括2×2小时的研讨会，每个部门的主管和2‐5名医护人员，以及医院的健康和安全人员制定了行动计划，以在1年的干预期内实施改善科室辅助设备使用的解决方案。工作场所社会资本：（a）团队内部（联结）；（b）团队与直接上级领导之间（链接A）；（c）团队与非直接领导之间（链接B）以及组织变革准备度在基线、6个月和12个月时进行测量。 结果: 所有结果指标均未出现 组间 交互作用。但是，事后的探索分析表明，在参与式干预后，群体内的社会资本和组织变革准备度的联系和和链接B有所改善。 结论: 参与式组织干预可以提高团队内部以及团队与非直接领导之间的社会资本和组织变革准备度。 影响: 在工作场所实施参与式干预可能是一项成本效益高的策略，因为它提供了额外的好处，例如增加了社会资本，改善了组织变革的准备度，这些好处超过了干预的主要成果。 试验注册: ClinicalTrials.gov（NCT02708550），2016年3月。